2021
DOI: 10.1002/hbm.25346
|View full text |Cite
|
Sign up to set email alerts
|

Reduced thalamic resting‐state functional connectivity and impaired cognition in acute abstinent heroin users

Abstract: As a critical component of cortico‐striato‐thalamo‐cortical loop in addiction, our understanding of the thalamus in impaired cognition of heroin users (HU) has been limited. Due to the complex thalamic connection with cortical and subcortical regions, thalamus was divided into prefrontal (PFC), occipital (OC), premotor, primary motor, sensory, temporal, and posterior parietal association subregions according to white matter tractography. We adopted seven subregions of bilateral thalamus as regions of interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…In our dFNC study, we further suggested reduced temporal variability in the functional efficiency of the thalamus, especially located in the ventroposterior medial region. In general, the ventroposterior medial thalamus is under inhibition of γ-aminobutyric acid (GABA) released from the thalamic reticular nucleus; this process was supposed to play a key role in controlling thalamocortical rhythm [ 81 , 82 ]. Moreover, aberrant thalamic firing, especially increased burst firing in the somatosensory thalamus without overall hyperactivity, has been proven to be associated with neuropathic pain [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our dFNC study, we further suggested reduced temporal variability in the functional efficiency of the thalamus, especially located in the ventroposterior medial region. In general, the ventroposterior medial thalamus is under inhibition of γ-aminobutyric acid (GABA) released from the thalamic reticular nucleus; this process was supposed to play a key role in controlling thalamocortical rhythm [ 81 , 82 ]. Moreover, aberrant thalamic firing, especially increased burst firing in the somatosensory thalamus without overall hyperactivity, has been proven to be associated with neuropathic pain [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings corroborate existing evidence that the insula is critically involved in craving and as such the development and maintenance of substance use disorders, including cocaine use disorder. 10,11,[13][14][15][16][17][18][19][20][45][46][47] Importantly, the association between stress-relief craving and right insular GMV was significantly moderated by sex: Although the association was negative in CU women, this association was positive in CU men. Although we expected these sex differences to be particularly pronounced in insular CT, these findings are in line with previous research that demonstrated that abstinence induced craving is negatively related to insular CT in nicotine dependent women, but positively related to insular CT in nicotine dependent men.…”
Section: Discussionmentioning
confidence: 95%
“…It can be seen that the thalamus is like an eraser that erases the memory of addiction. The two subregions of the thalamus are also involved in cognitive control and craving, revealing the implications of the thalamic subnucleus in the pathology of acute abstinent heroin users ( 104 ). Thus, the thalamus has become a new focus for solving drug addiction.…”
Section: Discussionmentioning
confidence: 99%